Pengaruh Media Sosial, Citra Destinasi dan Fasilitas terhadap Kepuasan Wisatawan di Objek Wisata Geopark Silokek Kabupaten Sijunjung - Magdalena, Maria; Fazilla, Nurul (ARZUSIN, 2026)
Tourist satisfaction is an important indicator in assessing the success of tourism destination management, including geopark-based tourist attractions. Although social media, destination image, and facilities have been widely studied in the tourism context, research that specifically discusses the influence of these three factors on tourist satisfaction at the Silokek Geopark Tourist Attraction in Sijunjung Regency remains limited. This study aims to analyze the influence of social media, destination image, and facilities on tourist satisfaction at the Silokek Geopark Tourist Attraction in Sijunjung Regency. This study used a quantitative approach with a survey method, involving 90 respondents selected through total sampling. Data were collected through questionnaire distribution and analyzed using regression statistical tests. The results show that social media has a positive and significant effect on tourist satisfaction, with the calculated t-value greater than the t-table value (2.132 > 1.987) and a significance value lower than 0.05 (0.036 < 0.05). Destination image and facilities also have a positive and significant effect on tourist satisfaction, with facilities showing a calculated t-value of 3.488 and a significance value of 0.001. These findings confirm that strengthening social media, destination image, and facilities plays an important role in increasing tourist satisfaction at geopark-based tourism destinations. The implications of this study provide a practical basis for the managers of the Silokek Geopark Tourist Attraction in designing digital promotion strategies, strengthening destination image, and improving the quality of facilities to support tourist satisfaction.